JURIDICAL REVIEW OF THE AUTHORITY OF THE CONSTITUTIONAL COURT IN RESOLUTION OF GENERAL ELECTION DISPUTES FOR REGIONAL HEAD: TINJAUAN YURIDIS KEWENANGAN PENGADILAN KONSTITUSI PENYELESAIAN SENGKETA PEMILIHAN UMUM KEPALA DAERAH - Micael Josviranto (SOSIOEDUKASI, 2020)
purpose of this research is to find out what is the legal basis for the authority of the Constitutional Court in resolving disputes over the results of the General Election of Regional Heads in Indonesia and how the effectiveness of the authority of the Constitutional Court in disputes over Regional Head General Election. The method used in this research is juridical normative, namely, the materials collected by conducting a literature study. The authority of the Constitutional Court in judging at the first and last levels whose decisions are final in deciding disputes regarding general elections, there are several paragraphs that discuss the extent to which the authority of the Constitutional Court in resolving disputes over the General Election of Regional Heads has been contained in Article 157 of Law Number 10 2016 concerning the Second Amendment to Law Number 1 of 2015 concerning Stipulation of Government Regulations in Lieu of Law Number 1 of 2014 concerning the Election of Governors, Regents and Mayors which form the legal basis for the authority of the Constitutional Court in resolving disputes over the results of the General Election in Indonesia.